Ion Sieve: Tailoring Zn2+ Desolvation Kinetics and Flux toward Dendrite-Free Metallic Zinc Anodes - Jiao, Shangqing; Fu, Jimin; Wu, Mingzai; Hua, Tao; Hu, Haibo (ACS nano, 2022)
Tip-induced dendrites on metallic zinc anodes (MZAs) fundamentally deteriorate the rechargeability of aqueous Zn metal batteries (ZMBs). Herein, an intriguing ion sieve (IS) consisting of 3D intertwined bacterial cellulose, deposited on the surface of MZAs (Zn@IS) through an in situ self-assembly route, is first presented to be effective in inhibiting dendrite-growth on MZAs. Experimental analyses together with theoretical calculations suggested that the IS coating can facilitate the desolvation of [Zn(H2O)6]2+ clusters via a strong interplay with Zn ions, weaken hydrogen evolution reaction of MZAs, and homogenize the ion flux with the abundant nanopores serving as ion tunnels, synergistically enabling dendrite-free Zn deposition on the Zn@IS anodes. Consequently, a lifespan up to 3000 h at a cutoff capacity of 0.25 mA h cm–2 was observed in a Zn@IS∥Zn@IS symmetric cell. In terms of application, pairing with a carbon-nanotube@MnO2 cathode as an example, the full ZMBs acquired enhanced rechargeability with much higher capacity retention over 73.3% after 3000 cycles compared to the counterpart with pristine MZA (21%).